2016
DOI: 10.1002/2015tc004027
|View full text |Cite
|
Sign up to set email alerts
|

The crustal structure of south central Mongolia using receiver functions

Abstract: The crustal thickness H and average crustal velocity ratio k (Vp/Vs) beneath south central Mongolia are investigated using the H-k stacking method based on teleseismic radial receiver functions. Our primary results reveal that the local crustal thickness varies from 38 to 46 km with an average value of 43 km. Thicker crust is found beneath the western Hentey Mountains, while thinner crust is located in the southern area of the Zuunbayan fault zone. The Bouguer gravity anomalies exhibit a strong correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 72 publications
(118 reference statements)
6
21
0
Order By: Relevance
“…The estimated thickness values at this location, ∼42–44 km, are consistent with He et al. (2016)'s receiver function study.…”
Section: Resultssupporting
confidence: 91%
“…The estimated thickness values at this location, ∼42–44 km, are consistent with He et al. (2016)'s receiver function study.…”
Section: Resultssupporting
confidence: 91%
“…Thus, station delays larger than 1.0 s may reflect the crustal thickness variations when the mean crustal velocities in this study areas are confined between 6.2 and 6.5 km/s. Stations located in western Mongolia and China with thick crust have relatively positive station delays, while stations located in eastern Mongolia and China with thin crust have negative station delays, which are consistent with previous observations by receiver functions (He et al, ; Li et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Our results demonstrate obvious low velocities beneath Hangay Dome and the Hentey Mountains (Figure ), where there are either no or slight low velocity anomalies from the study of Wang, Niu, et al (). However, low crustal Vp / Vs ratios (He et al, ) and low Lg wave attenuation (He, Sandvol, et al, ), together with the lack of Cenozoic basalts observed beneath the western Hentey Mountains, comprehensively suggest that the crust of the western Hentey Mountains is not strongly affected by the hot mantle materials. Thus, the mechanisms of low Pn velocities observed beneath the Hentey Mountains are obviously different with those in Hangay Dome and the Sayan Range, where Cenozoic volcanism and basalts are widely scattered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations